A Single Rolled‐Up Si Tube Battery for the Study of Electrochemical Kinetics, Electrical Conductivity, and Structural Integrity. (22nd October 2014) - Si, Wenping; Mönch, Ingolf; Yan, Chenglin; Deng, Junwen; Li, Shilong; Lin, Gungun; Han, Luyang; Mei, Yongfeng; Schmidt, Oliver G.
<x xml:space="preserve">Abstract</x> A lab‐on‐chip device is demonstrated for probing the electrochemical kinetics, electrical properties, and structure integrity of a single Si rolled‐up tube as the anode in lithium‐ion batteries. Cyclic voltammetry of the tube exhibits better‐resolved peaks than of the planar film due to the enhanced diffusion. The tube is wrinkled after cycling. The tube could be used as a promising ultra‐microelectrode for other voltammetry research. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>